Malaria and Lyme disease - the largest vector-borne US epidemics in the last 100 years: success and failure of public health - Ilia Rochlin; Dominick V. Ninivaggi; Jorge L. Benach (BMC, 2019)
Abstract Malaria and Lyme disease were the largest vector-borne epidemics in recent US history. Malaria, a mosquito-borne disease with intense transmission, had higher morbidity and mortality, whereas Lyme and other tick-borne diseases are more persistent in the environment. The responses to these two epidemics were markedly different. The anti-malaria campaign involved large-scale public works eradicating the disease within two decades. In contrast, Lyme disease control and prevention focused on the individual, advocating personal protection and backyard control, with the disease incidence steeply increasing since 1980s. Control of Lyme and other tick-borne diseases will require a paradigm shift emphasizing measures to reduce tick and host (deer) populations and a substantial R&D effort. These steps will require changing the political climate, perceptions and opinions to generate support among governmental levels and the general public. Such support is essential for providing a real solution to one of the most intractable contemporary public health problems.